2020
DOI: 10.3389/fchem.2019.00872
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Based Antimicrobial Delivery-Systems for the Treatment of Bacterial Infections

Abstract: Many nanotechnology-based antimicrobials and antimicrobial-delivery-systems have been developed over the past decades with the aim to provide alternatives to antibiotic treatment of infectious-biofilms across the human body. Antimicrobials can be loaded into nanocarriers to protect them against de-activation, and to reduce their toxicity and potential, harmful side-effects. Moreover, antimicrobial nanocarriers such as micelles, can be equipped with stealth and pH-responsive features that allow self-targeting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 111 publications
(128 reference statements)
1
86
0
3
Order By: Relevance
“…Bacterial biofilms are composed of bacteria aggregates, involved in an extracellular matrix, containing proteins, polysaccharides and DNA [ 9 ]. This structure provides an excellent mechanism of defense, against immune response and blocks the antibiotic penetration, leading to extended hospitalization periods and high social costs [ 8 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial biofilms are composed of bacteria aggregates, involved in an extracellular matrix, containing proteins, polysaccharides and DNA [ 9 ]. This structure provides an excellent mechanism of defense, against immune response and blocks the antibiotic penetration, leading to extended hospitalization periods and high social costs [ 8 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drug delivery systems play an important role to improve the safety and efficacy of loaded antibiotics, by allowing more appropriated pharmacokinetics and biodistribution profiles, thus improving the success of antimicrobial compounds already in clinical use [ 14 ]. Indeed, several nanotechnological platforms have been developed over the past decades, aiming to deliver the antibiotics at the infection sites and increase their penetration into biofilm structures [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The particle dispersed in an emulsion has a surface charge due to its attraction to a layer of oppositely charged particle; an electric double layer is thus generated [ 24 ]. An absolute value of zeta potential greater than 25 mV generally indicates a stable emulsion [ 21 , 37 , 38 , 39 ]. The zeta potentials of all nanoemulsions tested in this study were in the range –32.0 mV to –38.2 mV ( Table 1 ), which means that the w/o emulsion droplets were negatively charged.…”
Section: Resultsmentioning
confidence: 99%
“…Global stresses can be applied to biofilms by the addition of a stress-inducing component to the growth medium that can diffuse through the biofilm. For example, many antibiotics can easily diffuse through biofilms, yet highly charged or large antibiotics are prevented from diffusion, unless they are encased in special delivery systems (Diaz-Pascual et al 2019;Singh et al 2010;Tseng et al 2013;Wang et al 2020). Monitoring all individual cells in Vibrio cholerae biofilms during exposure to translational inhibitors revealed that these antibiotics could diffuse throughout the biofilm within minutes.…”
Section: Responses Of Biofilms To Global Stressmentioning
confidence: 99%